PEMANFAATAN POLYURETHANE DENGAN VARIASI VOLUME SEBAGAI PERKUATAN STRUKTUR DINDING BATA RINGAN RUMAH PENDUDUK DI KECAMATAN MIJEN KOTA SEMARANG: PEMANFAATAN POLYURETHANE DENGAN VARIASI VOLUME SEBAGAI PERKUATAN STRUKTUR DINDING BATA RINGAN RUMAH PENDUDUK DI KECAMATAN MIJEN KOTA SEMARANG - Widoanindyawati, Vemi; Triwardaya; Harprastanti, Primasiwi; Setiawan, Dedi Budi; Sismedi, Gud (Politeknik Negeri Semarang, 2025)
The vulnerability to earthquake hazards in Semarang City is still quite low. Many people have houses that are not yet standardized to the Indonesian National Standards (SNI). Mijen District, Semarang City, is one of the districts that is quite prone to earthquake hazards because of its location close to the source of the Kaligarang fault. Therefore, it is necessary to provide preventive measures and measures for community housing buildings. The house is an earthquake-resistant building and is able to withstand sudden ground movements. By building houses that comply with Indonesian National Standards, it is hoped that damage to the building will be minimized and there will be no loss of life. By using light building materials and strong adhesive between joints, it will increase the ability to withstand seismic loads in a building. In wall construction, you can apply light bricks with polyurethane adhesive because the load caused is relatively light. Apart from being able to strengthen the bond between each layer of brick properly, this adhesive is easy to apply. It is hoped that this adhesive material will be capable of gluing and creating a strong bond in the lightweight brick layers. Varying polyurethane volume is needed to determine the effective and efficient quantity of polyurethane to produce a strong bond. For this reason,